Complementarities, Coordination, and Culture - Christopher J. Ellis; Jon C. Thompson; Jiabin Wu (Center for Economic Studies and ifo Institute (CESifo), 2016)
We develop a new model of the intergenerational transmission of culture based on the labor market characteristics of different cultural types. Following Borjas (1994,1995) we assume that cultural heterogeneity increases labor productivity due to skill complementarities, however following Jackson and Xing (2014) we also assume that cultural heterogeneity hampers com-munication. We model this as a game in which individuals first engage in uniformly random matching, and then once matched play a coordination game. Other-type matches are thus potentially more productive, but also less likely to coordinate. We show that this set up can replicate many of the seminal results of Bisin and Verdier (2001) without assuming imperfect empathy. This means that we do not face the inherent difficulties that such models involve when making welfare statements. Further, we are able to obtain new results concerning the efficient size of a cultural minority, the effects of tax and welfare programs on the size and welfare of minorities, and the relationship between the intensity of social interaction and size and welfare of a minority. In an extension of the model we introduce “intermediaries” who may either facilitate other-type matching or improve after-match coordination. We then ask which parent population, the minority or majority, the intermediaries arise from and explore their implications for the equilibrium and welfare.
Keywords: A14; C73; D10; Z13; 330; cultural transmission; coordination games; social interaction; minorities; intermediaries; tax and welfare programs